Analisis Implementasi Kebijakan Vaksinasi COVID-19 di Kabupaten Batang Hari - Riana Agny Betry; Haerawati Idris; Yuanita Windusari (Jurnal Keperawatan Silampari, 2022)
This study aims to analyze the implementation of the COVID-19 vaccination policy in Batang Hari Regency. This research is a descriptive study through a qualitative approach with a case study research design. Based on the interview results, it is known that the implementation of the COVID-19 vaccination policy in Batang Hari Regency has been going well. Several indicators in policy implementation, such as communication, Human Resources (HR), bureaucratic structure, disposition, and performance, have been carried out well. However, it has several obstacles, such as vaccination stock, insufficient human resources when there is an accelerated invasion of vaccination, and vaccine recording and reporting to the public. Public health center. It can be concluded that overall communication, resources, disposition, bureaucratic structure, and implementation of vaccination policies have been carried out well and effectively. However, there are obstacles in practice, such as a shortage of human resources and a vaccination budget. Keywords: Disposition and Implementation, Communication, Resources, Bureaucratic Structure